O12 Simulating a Covid-19 patient journey through a teaching hospital: lessons learnt. (10th November 2020) - Rowson, Mark; Lloyd, Michael; Bennett, Nicholas
Abstract : Introduction: The COVID-19 pandemic has placed considerable demands on global healthcare. Where patients are admitted to hospital, they may require escalating levels of care across different departments. Healthcare staff needed to be able to manage these patients effectively, and simulation-based-training (SBT) can be used to prepare staff and organisations to review their systems for advanced planning. 1 2 Methods: A multi-professional simulation was implemented to replicate a patient transfer from ambulance, emergency department, ward area, intensive care and theatres. The simulation was led by experienced facilitators in early March 2020 prior to the UK endemic, and included practical elements of patient care including use of personal protective equipment (PPE) and intubation. Scenario participants were staff on shift at the time and included clerical, nursing, medical, anaesthetists and theatre staff, cleaners, porters, infection control and microbiologists. A live actor and SimMan 3G was used throughout the scenario which lasted for approximately six hours including a multi-professional debrief. Workflows were observed throughout and clinical leads asked to reflect on the event. The aim was to review systems and processes to support action plans for advance planning of Covid-19 patient workflow. Results: Three key areas for action were identified: Staff capability, communication, and systems and processes. For staff capability, knowledge of latest public health advice, use of PPE and donning and doffing techniques were incorrect. Communication and handover issues were identified across teams and difficulties in staff communication between isolation and non-isolation areas highlighted. Systems and process issues included difficulty in locating lift keys, incorrect sample bottles for blood gases, incorrect transfer of samples, lack of equipment for intubation, decontamination of lift areas and anaesthetic airway equipment. Other system issues included non-availability of security staff to clear transfer areas and design and capacity of emergency department covid-19 areas. Actions and outcomes following this event have included updated guidance and policies, intubation checklists, education and training of staff, departmental and equipment redesign, and cascade of updated information to support both patient and staff safety. Discussion and Conclusion: SBT can test response to situations in a safe environment before they occur. 1 By simulating a COVID-19 patient journey, SBT can identify performance gaps and latent safety threats to inform practice. This COVID-19 simulation demonstrates the value of SBT to test hospital systems for advance planning of and preparation for emergencies and critical incidents to support both patient and staff safety. References: Lloyd M, Watmough S, Bennett, N. Simulation-based training: applications in clinical pharmacy. Clinical Pharmacist 2018;10(9): 3–10. LeBlanc VR, Manser T, Weinger MB, Musson D, Kutzin J, Howard SK. The study of factors affecting human and systems performance in healthcare using simulation. Simul Healthc 2011;6:S24e9.